X-Ray Lasers 2016 Proceedings of the 15th International Conference on X-Ray Lasers (Springer Proceedings in Physics, 2018)
These proceedings comprise a selection of invited and contributed papers presented at the 15th International Conference on X-Ray Lasers (ICXRL 2016), held at the Nara Kasugano International Forum, Japan, from May 22 to 27, 2016. This conference was part of an ongoing series dedicated to recent developments in the science and technology of x-ray lasers and other coherent x-ray sources with additional focus on supporting technologies, instrumentation and applications. The book showcases recent advances in the generation of intense, coherent x-rays, the development of practical devices and their applications across a wide variety of fields. It also discusses emerging topics such as plasma-based x-ray lasers, 4th generation accelerator-based sources and higher harmonic generations, as well as other x-ray generation schemes.